Moisture pulse-reserve in the soil-plant continuum observed across biomes. (December 2018) - Feldman, Andrew; Short Gianotti, Daniel; Konings, Alexandra; McColl, Kaighin; Akbar, Ruzbeh; Salvucci, Guido; Entekhabi, Dara
Abstract The degree to which individual pulses of available water drive plant activity across diverse biomes and climates is not well understood. It has previously only been investigated in a few dryland locations. Here, plant water uptake following pulses of surface soil moisture, an indicator for the pulse–reserve hypothesis, is investigated across South America, Africa and Australia with satellite-based estimates of surface soil and canopy water content. Our findings show that this behaviour is widespread: occurring over half of the vegetated landscapes. We estimate spatially varying soil moisture thresholds at which plant water uptake ceases, noting dependence on soil texture and proximity to the wilting point. The soil type and biome-dependent soil moisture threshold and the plant soil water uptake patterns at the scale of Earth system models allow a unique opportunity to test and improve model parameterization of vegetation function under water limitation. Water content in plants increasing while the surrounding soil moisture decreases, measured through remote sensing on multiple continents, may be suggestive of a pulse–reserve mechanism that has not been observed on a large spatial scale before. This behaviour, triggered or rendered inactive by certain thresholds, is seen in biomes other than arid lands.